2014
DOI: 10.3892/ijmm.2014.1963
|View full text |Cite
|
Sign up to set email alerts
|

The downregulation of miR-144 is associated with the growth and invasion of osteosarcoma cells through the regulation of TAGLN expression

Abstract: Alterations in the expression of microRNAs (miRNAs or miRS) have been implicated in the pathogenesis of the majority of human malignancies, and the dysregulation of microRNA-144 (miR-144) has been associated with several diseases. However, the potential involvement of miR-144 in osteosarcoma, a common malignant bone tumor in children and adolescents with a high risk of relapse and metastasis, has not yet been fully investigated. In the present study, we examined the expression and roles of miRNAs in osteosarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 45 publications
2
31
0
1
Order By: Relevance
“…miRNAs function via base pairing with complementary sequences within mRNA molecules [20,21,22,23], cutting off the mRNA molecule on target genes, or inhibiting translation of target genes. Some research has indicated that miR-144 is downregulated in many cancers [24,25,26,27,28,29,30,31]. These previous findings coincide with our results, which identified that miR-144 is significantly downregulated in human lung cancer.…”
Section: Discussionsupporting
confidence: 83%
“…miRNAs function via base pairing with complementary sequences within mRNA molecules [20,21,22,23], cutting off the mRNA molecule on target genes, or inhibiting translation of target genes. Some research has indicated that miR-144 is downregulated in many cancers [24,25,26,27,28,29,30,31]. These previous findings coincide with our results, which identified that miR-144 is significantly downregulated in human lung cancer.…”
Section: Discussionsupporting
confidence: 83%
“…The role of miR-144 in osteosarcoma has recently been reported. Zhao et al found that miR-144 may regulate osteosarcoma cell proliferation and invasion by downregulating its target gene, TAGLN [26]. Our study focuses on the role of miR-144 in proliferation, apoptosis, invasion and migration of human osteosarcoma F5M2 cell line, and the interaction between miR-144 with Ezrin protein.…”
Section: Introductionmentioning
confidence: 93%
“…Multiple genes were upregulated or downregulated, as determined by miRNA microarray. MiRNA expression changes before and after tumor treatment can be used to detect chemotherapy sensitivity (Zhao et al, 2014;Xiao et al, 2015). MiR-184 is a novel miRNA, and its role in tumors remains unclear.…”
Section: Discussionmentioning
confidence: 99%